Regularities of Deposition and Wear of Electrospark Deposited Coatings of NiAl-CrB2 System. - Українець, М.С. (Problems of Tribology, 2016)
Ukrainets M. Regularities of Deposition and Wear of Electrospark Deposited Coatings of NiAl-CrB2 System. NiAl has considerable scientific interest as an electrode material for heat-resistant coatings obtaining using electro-spark alloying. Chromium diboride reinforcing additive introducing into intermetallic in order to improve the wear resistance of such coatings is reasonable. The electrodes of the NiAl-CrB2 system with 15-45 wt.% of chromium diboride additives were obtained by hot pressing. The influence of the CrB2 additive amount on the technological parameters of the alloying process was studied. The wear rate of the obtained coatings was determined by «pin-on-disc» scheme at T = 500° C. It was shown that the CrB2 introduction into NiAl leads to a significant increase of intermetallic wear resistance. Worn surfaces were studied and the regularities of obtained coating wear were determined. Keywords: ESA, intermetallic, NiAl, diboride, CrB2, high-temperature sliding, wear resistance.